Makna Simbolik Gerak Tari Kebo Kinul di Desa Genengsari Kabupaten Sukoharjo - Adiba Ussy Admaja; R. Indriyanto (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Based on the research that has been explained, Kebo Kinul Dance is a traditional art form that developed from folklore closely connected to the daily lives of local people and village traditions, such as the earth alms ceremony. This dance evolved from symbolic representations of community activities, particularly the hard work of farmers in the rice fields, which were later transformed into a dance performance by residents and artists. The essence of the Kebo Kinul movements is derived from everyday community activities. For example, the footsteps symbolize the movements of buffaloes, the shoulder movements represent the strength of the buffalo, and the rotating movements convey energy and enthusiasm. The stiff movements are not considered a weakness of the dance; instead, they have become one of its distinctive characteristics. In addition, the use of costumes made from straw further strengthens the identity and uniqueness of the dance. Furthermore, the costumes and performance forms contain figurative meanings that illustrate the relationship between humans, animals, and the surrounding environment. In general, Kebo Kinul Dance is not merely a form of entertainment, but also symbolizes persistence, togetherness, humility, and gratitude to the Creator for the harvest and the life that have been received